1967
DOI: 10.1677/joe.0.0390345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin and 5-Hydroxytryptamine on Aldosterone and Corticosterone Production by Adrenal Glands of Normal and Hypophysectomized Rats

Abstract: The effects of subcutaneous injections of melatonin (50, 100 and 200 \ g=m\ g. / 100 g. body weight) and 5-hydroxytryptamine (100, 200 and 400 \g=m\g./100g.) on the production of aldosterone and corticosterone by the adrenal glands of intact and hypophysectomized adult male rats were investigated.Melatonin increased the production of corticosterone significantly and depressed simultaneously the production of aldosterone. In the hypophysectomized rats, melatonin was without effect. 5-Hydroxytryptamine increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…This Þnding is supported by reports on the lack of any e¤ect of melatonin on corticosterone production in perfused adrenal glands in vitro (Persengiev et al 1989) and on adrenal growth and cortisol secretion in vivo (Gromova et al 1967;Malendowicz 1985) and humans (Wright et al 1986;Waldhauser et al 1987;Nickelsen et al 1989). Also, the light-induced suppression of nocturnal melatonin secretion had no e¤ect on circulating cortisol in men (McIntyre et al 1992).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This Þnding is supported by reports on the lack of any e¤ect of melatonin on corticosterone production in perfused adrenal glands in vitro (Persengiev et al 1989) and on adrenal growth and cortisol secretion in vivo (Gromova et al 1967;Malendowicz 1985) and humans (Wright et al 1986;Waldhauser et al 1987;Nickelsen et al 1989). Also, the light-induced suppression of nocturnal melatonin secretion had no e¤ect on circulating cortisol in men (McIntyre et al 1992).…”
Section: Discussionmentioning
confidence: 65%
“…Others used isolated pineals or cultured pinealocytes and isolated adrenals or adrenomedullary tissue to study the mutual inßuences of glucocorticoids and melatonin on each others synthesis and release (Giordano et al 1970;Ogle and Kitay 1978;Sanchez de la Pena et al 1983;Touitou et al 1989). It is worth mentioning that the concept of a physiological coupling between glucocorticoid and melatonin secretion has already been questioned by some earlier studies (Gromova et al 1967;DeussenSchmitter et al 1976;Champney et al 1985;Malendowicz 1985;Wright et al 1986;Persengiev et al 1989). Apparently, the more the experimental design chosen by experimentors to explore the putative interactions between both endocrine systems approached reality, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinealectomy has been reported to cause adrenal hypertrophy in rodents [1][2][3][4][5][6] and this effect is neutralized by adminis-tration of pineal extract or melatonin [1,3]. Pinealectomy increases corticosterone secre tion [7][8][9] and disturbs the 24-hour pattern of adrenal activity [6,10], while melatonin treatment has been reported both to increase [10,11] and decrease corticosterone [12][13][14], Pinealectomy also decreases and melatonin administration in vivo in the female rat stimulates 5a-reductase activity in the adre nal gland resulting in an alteration of the proportions of steroids subsequently pro duced by adrenal slices [4,5], Long-term melatonin treatment also causes hypertrophy of the zona glomerulosa and a rise in plasma aldosterone [15],…”
Section: Introductionmentioning
confidence: 99%
“…Using the rate at which 1311 disappears from the thyroid as an index, Turner and his associates have concluded that melato nin also slows the secretion of iodinated thyroid hormones (89,(102)(103)(104). Some investigators have observed in vivo decreases in adrenal corticosterone production in rats given large doses of melatonin (50-200 I-'-gliOO g body weight) (105). Others, using smaller doses, have failed to observe changes in either the synthesis of corticosterone or the plasma or pituitary levels of ACTH (1 I-'-g/kg body weight) (106).…”
Section: Other Glandsmentioning
confidence: 99%